The Economy in Context: A Value-Based Approach - Arjo Klamer (Journal of Contextual Economics – Schmollers Jahrbuch, 2020)
A more comprehensive picture, or imaginary in Charles Taylor's term, puts the spheres of market and organizations in a broader perspective. It calls for new concepts – like shared and common goods or practices – and the willingness to contribute. We see that culture, in the sense of sense-making practices, matters a great deal, just as Deirdre McCloskey and Virgil Storr, among others, argue. By focusing on values, we see that people valorize their values not just by way of markets, but more so by way of different, non-market spheres. The article reflects a value-based approach to economics and the economy.
Keywords: A1; B5; Z1; 330; Value-Based Approach; Social Goods; Cultural Goods; Shared Goods; Willingness to Contribute; Culture; Oikos